Human Capital and Financial Management Practices Effect on Coffee Cooperatives Performance in Ethiopia - Mershaye Birhane; Chalchisa Amentie; Brehanu Borji; Shashi Kant (International Journal of Applied Economics, Accounting and Management (IJAEAM), 2023)
The study's main topic was how Ethiopian coffee cooperatives' financial management practises and organisational performance are mediated by human capital. The cross sectional study with multistage sampling was employed by the researchers. KMO was employed as a test for adequate data. To evaluate the overall impact of the regression, total variance was used. To determine if the observable variables could adequately explain the latent determinants, confirmatory factor analysis was utilised. The model fitness and mediation analysis were both tested using SEM. According to study, there was a significant link based on the data because the KMO value of.906 was greater than 0.5 and the statistical threshold for the Bartlett's test was lower than 0.05. The researchers discovered that the CMIN/DF was less than 3.0, indicating model acceptance. The model being tested is compared using the Tucker Lewis Index (TLI). co-ops for coffee Human capital has led to a roughly 75% boost in performance. As a result, there is now some partial mediation between financial management practises and coffee cooperative performance.